The BSC as a support vector for the strategic management process of organizations: a systematic literature review - JELLOULI , Tarik; KSIR , Yassir (Revue du contrôle, de la comptabilité et de l’audit, 2022)
The literature about the BSC as a support vector for the strategic management process of companies has evolved exponentially over the last few decades. However, the divergence of research results means that the role of this tool in strategic deployment is still poorly understood. Based on a systematic review of empirical studies published between 1992 and 2020, this article proposes a framework that brings together a set of variables related to the strategic management process (strategic planning, strategy implementation and strategic decision-making) and its different stages. The ensuing results highlight several findings that would allow managers and decision-makers to better understand the contribution of this dashboard in terms of strategic management and researchers to better channel their efforts in studying this tool through the exploitation of the systematic literature review presented which provides a framework for the impact of the use of BSC on the strategic management of organizations.